2020
DOI: 10.1111/pce.13777
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomic markers and physiological adaptations for high phosphate utilization efficiency in rice

Abstract: Utilizing phosphate more efficiently is crucial for sustainable crop production. Highly efficient rice (Oryza sativa) cultivars have been identified and this study aims to identify metabolic markers associated with P utilization efficiency (PUE). P deficiency generally reduced leaf P concentrations and CO 2 assimilation rates but efficient cultivars were reducing leaf P concentrations further than inefficient ones while maintaining similar CO 2 assimilation rates. Adaptive changes in carbon metabolism were det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 39 publications
1
14
0
Order By: Relevance
“…Any potentially preferential allocation to roots rather than developing leaves in the high-PUE genotypes did, however, not reduce the biomass of leaves in these genotypes in comparison to the low-PUE genotypes ( S3 Fig ). Thus, the high-PUE genotypes appeared to more rapidly reduce P concentrations in newly developed and older leaves alike, and likely allocated the extra P to root growth, which would be an efficient strategy to outgrow P deficiency as new roots will increase the amount of P taken up by the plant [ 29 , 30 ] investigated to what extent reduced leaf P concentrations affect leaf photosynthetic efficiency. At the range of P concentrations seen here at T2 in the high-PUE genotypes (< 1.0 mg g -1 ) one may expect reductions in CO 2 assimilation rates by up to 30% and these will be less in IR64 and Taichung with leaf P concentrations well-above 1.0 mg g -1 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Any potentially preferential allocation to roots rather than developing leaves in the high-PUE genotypes did, however, not reduce the biomass of leaves in these genotypes in comparison to the low-PUE genotypes ( S3 Fig ). Thus, the high-PUE genotypes appeared to more rapidly reduce P concentrations in newly developed and older leaves alike, and likely allocated the extra P to root growth, which would be an efficient strategy to outgrow P deficiency as new roots will increase the amount of P taken up by the plant [ 29 , 30 ] investigated to what extent reduced leaf P concentrations affect leaf photosynthetic efficiency. At the range of P concentrations seen here at T2 in the high-PUE genotypes (< 1.0 mg g -1 ) one may expect reductions in CO 2 assimilation rates by up to 30% and these will be less in IR64 and Taichung with leaf P concentrations well-above 1.0 mg g -1 .…”
Section: Discussionmentioning
confidence: 99%
“…At the range of P concentrations seen here at T2 in the high-PUE genotypes (< 1.0 mg g -1 ) one may expect reductions in CO 2 assimilation rates by up to 30% and these will be less in IR64 and Taichung with leaf P concentrations well-above 1.0 mg g -1 . While this can be compensated to some extent in high-PUE genotypes by producing larger leaves [ 30 ], we may expect the loss of photosynthetic capacity to be more pronounced in the high-PUE genotypes. In this regard one needs to keep in mind that the strategy to preferentially supply P for root growth does not provide additional P uptake in this nutrient solution experiment, while it would do so in plants grown in soil.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The change of internal small molecular compounds can occur earlier than changes in external characteristics [37]. Previous studies only focused on the changes of metabolites under single nutrient stress, such as nitrogen, phosphorus, potassium or zinc [17][18][19][20]38]. In fact, different nutritional stress can cause changes of the same metabolites.…”
Section: Discussionmentioning
confidence: 99%
“…Cevallos-Cevallos et al [18] found significant differences in oxo-butanedioic acid, arabitol, and neo-inositol between zinc-deficient and healthy orange trees. The metabolomics of rice leaves under conditions of nitrogen and phosphorus deficiencies were analyzed by Shen [19] and Watanabe et al [20], the stress-resistant substances and amino acid substitution products increased under nitrogen deficiency, with sinapate, benzoate, and glucuronate related to phosphorus deficiency.…”
Section: Introductionmentioning
confidence: 99%